TAZKIYAH AL-NAFS SEBAGAI RUH REKONSTRUKSI SISTEM PENDIDIKAN ISLAM - Mohammad Muchlis Solichin (TADRIS: Jurnal Pendidikan Islam, 2009)
Islamic education ia a mean of value transmission and islamic doctrines to the students in order to understand, internalize, and practice the islamic doctrines precisely. Meanwhile, the core of islamic doctrines is to implant good morals. And this the prophetic mission of Muhammad SAW, prefecting morals of humans. Inserting good morals as the soul of developing the planning, actuating, and evaluating islamic education. These efforts are very crucial to avoid misleading orientation of islamic education as mastering knowledge only (Islamology) without understanding, penetrating, and actuating in daily life. The efforts to reconstruct islamic educaton as exsplain above can be carried out by formulating instructional goals, designing curriculum, and implementing Islam by referring to pervading good morals (akhlak) through tazkiyah al-nafs.